Financial Market Effects of FOMC Communication: Evidence from a New Event-Study Database - Miguel Acosta; Andrea Ajello; Michael D. Bauer; Francesca Loria; Silvia Miranda-Agrippino (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This paper introduces the U.S. Monetary Policy Event-Study Database (USMPD), a novel, public, and regularly updated dataset of financial market data around Federal Open Market Committee (FOMC) policy announcements, press conferences, and minutes releases. Using the rich high-frequency data in the USMPD, we document several new empirical findings. Large monetary policy surprises have made a comeback in recent years, and post-meeting press conferences have become the most important source of policy news. Monetary policy surprises have pronounced negative effects on breakeven inflation based on Treasury yields. Risk assets, including dividend derivatives, also respond strongly and negatively to monetary policy surprises, consistent with conventional channels of monetary transmission. Press conferences have stronger effects than FOMC statements on most asset prices. Finally, the term structure evidence shows peak effects on market-based inflation and dividend expectations at horizons of several years.
Keywords: E43; E52; E58; 330; Federal Reserve; monetary policy surprises; high-frequency event studies